Analisis Promosi, Word Of Mouth Dan Citra Merek Pengaruhnya Terhadap Minat Beli Pada Pengunjung Di Toko Qolsa Metro - Vivi Ardilia Sari; Nina Lelawati; Nani Septiana; Iqbal Mei Setiawan (Universitas Muhammadiyah Metro, 2025)
Based on the tests that have been carried out by researchers using data analysis techniques using tests (validity test and reliability test) testing requirements analysis using (normality test and multiple linear regression analysis test) and hypothesis testing using (t test, significant F test and F test the coefficient of determination R2) gets the result that only promotion and word of mouth variables have a significant influence on purchase intention, while the image variable does not influence and is not significant on purchase intention. Likewise for the simultaneous tests that have been carried out, the results show that the variables that influence buying interest are only 43.4%.